Nilai-nilai Fiqih dalam Membangun Karakter Peserta Didik di SD/MI - Nasri Nasri (Pendidikan Guru Madrasah Ibtidaiyah STIT Palapa Nusantara, 2018)
The search for thoughts about the education of fiqh, where fiqh inquiry has in essence has a great significance for the continuity of education in the modern era as nowadays. Besides, this research also to be used as an information material for the community of the importance of the meaning of fiqh education for life, especially in order facing modern life that has tendency of waning of values or norms of law in order of life of society also as material of information and documentation for planner and educational designer, Values in Islam contain two categories of meaning seen from normative aspect, that is good and bad. The spiritual values of jurisprudence have a close connection with a day's amaliah especially concerning worship to God. The value of jurisprudence is also a spirit (spirit) to go to the pleasure of Allah. Spiritual fiqih were extracted from two ways namely; Through faith and piety and through worship Building the Islamic character departs from two ways closely related to the basic of akhlaki. The concept of pious faith is the foundation of all activities while the concept of worship centers on an important basic principle that man was created as the holder of the mandate of Allah Almighty. who carries the treatise and exercises His Shari'a.